The Interaction Among Lithuanian Folk Dance Ensembles in the Context of Cultural Education: Directors’ Attitude - Čyplytė, Raminta (Pedagogika, 2014)
The article aims to reveal features and expression of the interaction between the state song and dance ensemble “Lietuva” and folk dance ensembles of higher education institutions in the process of youth cultural education. Since this aspect has not been analyzed in detail, the research was held among directors of folk dance ensembles of higher education institutions and the state song and dance ensemble „Lietuva“ and attempted to reveal two perspectives. The questioning of the directors showed that the interaction between ensemble “Lietuva” and folk dance ensembles of high schools in the context of youth cultural education exists and appears through folk dance ensembles connecting factors such as: genre of folk dance, common cultural activities and repertoire as well as common content of education which includes teaching methods, dance technique and its evaluation, other problems and relevant topics which forces to attract attention to the peculiarity of folk dance and its promotion in the contemporary cultural context. Directors of the ensemble “Lietuva” and high school ensembles stated that the ensemble “Lietuva” is still relevant today and actively participate in the cultural education of young people through folk dance, song and music hereby preserving national traditions and customs.